Penerapan Polluter Pays Principle dalam Perkara Tumpahan Minyak di Teluk Kota Balikpapan - Kana Kurnia; Indra Rizqullah Fawwaz; Lita Herlina (Jurnal Hukum IUS QUIA IUSTUM, 2023)
The environmental pollution that occurred in Balikpapan Bay was the result of a pipe leak caused by PT Pertamina (Persero) Refinery Unit V, where this is the largest environmental pollution occurring with the impact of an oil spill that threatens the sustainability of the ecosystem in the sea and the coastal communities of the bay of Balikpapan City. This study aims to analyse how the polluter pays principle is regulated in Law Number 32 of 2009 on Environmental Protection and Management as well as identifying and applying this principle to environmental pollution that occurs in Balikpapan Bay. The method used in this research is normative juridical thus the data used is secondary data collected through literature study. The results of this research are, firstly, the polluter pays principle regulated in Article 87 of Law Number 32 of 2009, which states that business actors who pollute the environment are obliged to allocate funds for activities to improve the environment they have polluted. Second, PT. Pertamina (Persero) Refinery Unit V, apart from being subject to compensation, must also be responsible for taking legal action such as installing or repairing waste processing units in accordance with specified environmental quality standards, restoring environmental functions, eliminating or destroying the causes of pollution and/or damage to the environment, and provide compensation or compensation to communities affected by oil spills.Keywords: Polluter Pays Principle; Polluter Pays Principle; Environmental Law Enforcement. AbstrakPencemaran lingkungan yang terjadi di teluk Balikpapan merupakan akibat dari kebocoran pipa PT. Pertamina (Persero) Refinery Unit V yang di mana pencemaran tersebut merupakan pencemaran lingkungan yang terbesar terjadi dengan dampak tumpahan minyak mengancam keberlangsungan ekosistem di laut dan masyarakat pesisir teluk Kota Balikpapan. Kajian ini bertujuan untuk mengetahui bagaimana pengaturan polluter pays principle dalam Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup serta mengidentifikasi dan menerapkan prinsip ini terhadap pencemaran lingkugan yang terjadi di Teluk Kota Balikpapan. Metode yang digunakan pada penelitian ini adalah penelitian yuridis normatif sehingga data yang digunakan adalah data sekunder yang dikumpulkan melalui studi pustaka. Hasil penelitian ini, pertama, polluter pays principle termuat dan diatur dalam Pasal 87 Undang-Undang Nomor 32 Tahun 2009 yang di mana para pelaku usaha yang mencemarkan lingkungan wajib mengalokasikan dana untuk kegiatan-kegiatan guna memperbaiki lingkungan yang telah dicemarkannya. Kedua, PT. Pertamina (Persero) Refinery Unit V selain dikenakan ganti rugi, juga harus bertanggung jawab untuk melakukan tindakan hukum seperti memasang atau memperbaiki unit pengolahan limbah sesuai dengan baku mutu lingkungan hidup yang ditentukan, memulihkan fungsi lingkungan hidup, menghilangkan atau memusnahkan penyebab pencemaran dan/atau perusakan lingkungan hidup, dan memberikan kompensasi atau ganti rugi kepada Masyarakat yang terdampak tumpahan minyak.Kata kunci: Asas Pencemar Membayar; Polluter Pays Principle; Penegakan Hukum Lingkungan.